Effectiveness of Health Education Campaigns on Antenatal Care Utilization in Low- and Middle-Income Countries: A Systematic Review - Chiamaka Cynthia Ekeoba (African Journal of Medicine, Surgery and Public Health Research, 2026)
Maternal and child health remains a critical public health priority in many low- and middle-income countries (LMICs), where insufficient utilization of antenatal care (ANC) services contributes to preventable maternal and neonatal morbidity and mortality. According to the World Health Organization, approximately 287,000 women die each year from pregnancy-related complications, with most deaths occurring in resource-limited settings where access to essential maternal health information and services remains inadequate. Health education campaigns have therefore been increasingly implemented as strategic interventions to improve awareness, influence health-seeking behavior, and encourage timely ANC utilization. This systematic review aims to synthesize available evidence on the effectiveness of health education campaigns in promoting ANC utilization among women in LMICs. A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2010 and 2025 using search terms related to health education campaigns, maternal health promotion, antenatal care utilization, and health communication interventions. Studies reporting quantitative or qualitative evidence on the influence of health education strategies, including mass media initiatives, community outreach programs, and digital communication platforms, on ANC attendance, early ANC booking, and completion of recommended visits were included. Extracted data were synthesized narratively, and patterns of intervention effectiveness were summarized across studies. A total of 29 studies conducted across different LMIC contexts met the inclusion criteria. The findings indicate that well-designed health education campaigns significantly improve maternal health knowledge and positively influence ANC attendance, particularly when interventions incorporate culturally appropriate communication approaches and community engagement strategies. This review concludes that health education campaigns can serve as effective maternal health promotion strategies for improving ANC utilization in resource-limited settings. The findings contribute to evidence on health communication interventions and provide practical implications for policymakers, public health practitioners, and maternal health programs seeking to strengthen ANC uptake among women in LMICs.